One-pot synthesis of polyhydropyridine derivatives via Hantzsch four component condensation in water medium: Use of a recyclable Lewis acid [Ce(SO4)2.4H2O] catalyst - Elaheh Mosaddegh; Asadollah Hassankhani (Bulletin of the Chemical Society of Ethiopia, 2012)
An efficient and eco-friendly method for the synthesis of polyhydroquinoline derivatives using Ce(SO4)2.4H2O as mild and heterogeneous Lewis acid catalyst via the Hantzsch reaction in very short reaction time is reported. A mixture of an appropriate aldehyde, dimedone, ethyl acetoacetate and malononitrile in the presence of the Ce(SO4)2.4H2O at reflux conditions in water based media resulted in good to excellent yields of the corresponding products. The catalyst can be used as selective for some aromatic aldehydes in the reaction conditions.DOI: http://dx.doi.org/10.4314/bcse.v26i3.16